Severe angiostrongyliasis with neuropsychiatric symptoms in vulnerable adults: Early diagnosis via next-generation sequencing and successful treatment - Xiaomiao Tang; Juanjuan Wu; Yefeng Yang; Yingqiong Wang; Chengji Jin; Chengzhi Xie; Mei Wang; Run Liu; Xiaozhi Wang; Fengyun Wang; Jing Wang (Journal of Infection and Public Health)
Angiostrongylus cantonensis (AC) is a parasite that occasionally infects humans, causing eosinophilic meningitis (EM). In this study, we identified two adult males with severe angiostrongyliasis being treated at the ICU. Both presented with mental and behavioral abnormalities and were initially treated for psychiatric disorders before showing symptoms like cough, fever, and altered consciousness. Patient 1, a homeless individual, presented with elevated eosinophil levels and typical meningitis symptoms, prompting an early diagnosis of EM that was later confirmed via next-generation sequencing (NGS) of the cerebrospinal fluid. Patient 2, who had schizophrenia as a pre-existing condition, did not exhibit the typical signs of meningitis but was nonetheless detected via NGS. Both patients responded well to corticosteroids and anthelmintics. A review of case reports underscores heightened infection risks among children with pica and vulnerable adults, including those with mental disorders or homelessness. The use of NGS is effective for the early diagnosis and treatment of severe angiostrongyliasis, especially in those with atypical symptoms.